The truth‐telling issue and changes in lifestyle in patients with cancer - Kostopoulou, V (BMJ Group, 2006)
OBJECTIVE: To compare the attitudes of patients with cancer toward making changes in lifestyle, according to their awareness of the diagnosis. METHOD: Personal interviews with 50 patients with breast cancer, 24 patients with prostate cancer and 50 patients with colorectal cancer were conducted in a cancer hospital in Athens, Greece. ANALYSIS: Multiple logistic regression models were used to estimate the odds ratio as a measure of the association of the characteristics of participants with changes in lifestyle. RESULTS: Overall, 22.6% of the patients were not aware of the diagnosis. Among the changes in lifestyle, 41.1% reported changing their diet to a healthier one, 22.6% of the smokers reduced or stopped smoking and 13.7% added new physical activity. Compared with uninformed patients, those who were aware of the diagnosis, after adjusting for the confounding effect of educational status (an index of socioeconomic status), were 2.5 times as likely to make dietary changes (p<0.1). Among the other characteristics under study, older patients were less likely to add new physical activity than younger ones (p<0.01), and newly diagnosed patients were more likely to stop or reduce smoking (p<0.1) than patients with a diagnosis made more than 12 months previously. CONCLUSION: Patients with cancer are motivated to attempt changes in lifestyle and can benefit from more factual information about the diagnosis.